2018
DOI: 10.1111/ijcp.13051
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated warfarin care programme results in superior warfarin control in Queensland, Australia

Abstract: Australian warfarin control was good when managed by either GP or WCP, but WCP management increased TTR by 13%. Dedicated warfarin programmes can improve warfarin control and optimise therapy for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…In this study no statistical difference was found in TTR according to the number of PK interacting medications and, in most cases, the TTR was above 80%. This is a relatively high TTR but consistent with previous research at this warfarin care management program regarding TTR of around 80% [31] with no influence on TTR from concurrent medication [32]. Poor warfarin control has been reported as a reason for changing from warfarin to NOAC therapy but, independent of TTR, the lower risk of intracranial bleeding and haemorrhagic stroke with NOACs may support a decision to switch from warfarin to NOACs [33].…”
Section: Discussionsupporting
confidence: 85%
“…In this study no statistical difference was found in TTR according to the number of PK interacting medications and, in most cases, the TTR was above 80%. This is a relatively high TTR but consistent with previous research at this warfarin care management program regarding TTR of around 80% [31] with no influence on TTR from concurrent medication [32]. Poor warfarin control has been reported as a reason for changing from warfarin to NOAC therapy but, independent of TTR, the lower risk of intracranial bleeding and haemorrhagic stroke with NOACs may support a decision to switch from warfarin to NOACs [33].…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the mean TTR was 81% whilst managed by the WCP and 69% whilst managed by the GP. Previous work by this research team compared two models of Australian warfarin management and produced similar results plus further investigated possible factors contributing to the differences in control [23]. Similar to this, recent Australian observational studies have reported warfarin TTR from 69% to 81% [9,24,25] depending on the management model.…”
Section: Discussionsupporting
confidence: 52%
“…The reduced TTR with aspirin is particularly noteworthy given the high level of warfarin control in this study, namely a mean above 80%. This study was conducted in a dedicated warfarin programme which has been shown to have particularly good warfarin control and levels above other management models, such as by general practitioners, which are more around the standard 70% TTR . A limitation of this study is that sub‐analyses could not be performed in patients with good and poor control as only 13% of patients with no other interacting drugs had a TTR < 70% (data not shown).…”
Section: Discussionmentioning
confidence: 99%